A novel statherin-derived phosphomimetic peptide (DDSt15) presents affinity for hydroxyapatite and effectively protects against intrinsic dental erosion - Ferrari, Carolina Ruis; Netz, Paulo Augusto; Kitamoto, Karolyne Sayuri de Araujo; Zonta, Anna Clara de Mello; Barros, Hannah Zomignan; Francese, Monique Malta; Ventura, Talita Mendes Oliveira; Taira, Éven Akemi; Marchetto, Reinaldo [UNESP]; Buzalaf, Marília Afonso Rabelo (Elsevier, 2025)
This study aimed to investigate the interaction mechanisms of the statherin derived phosphomimetic peptide (DDSt15) with hydroxyapatite through molecular dynamics simulations and Quartz Crystal Microbalance with Dissipation Monitoring (QCM-D) analysis and evaluate its protective effect against intrinsic enamel erosion in vitro. The peptide was engineered by mutating two residues in the statherin derived peptide (StatpSpS), and its topology was established using CHARMM-GUI for GROMACS simulations. A 500 ns molecular dynamics simulation assessed the peptide's behavior with hydroxyapatite. Additionally, DDSt15 was synthesized using a solid-phase method. Interactions of DDSt15 with saliva and hydroxyapatite surface were analyzed using QCM-D to evaluate the effect of acquired pellicle enrichment with this peptide. In vitro experiments were performed on bovine enamel samples treated with concentrations of DDSt15 at 0.94 × 10⁻⁵ M, 1.88 × 10⁻⁵ M, 3.76 × 10⁻⁵ M, and 1.88 × 10-5 M StatpSpS, with negative and positive control groups receiving deionized water and the commercial solution Elmex Erosion Protection®, respectively. Erosive challenges were applied using 0.01 M hydrochloric acid (pH 2.3) once/day for 3 consecutive days, and enamel hardness and reflection intensity were assessed pre- and post-treatment. Results indicated that DDSt15 exhibited affinity for the hydroxyapatite surface, and the pellicle formed with DDSt15 demonstrated significant properties, as observed in QCM-D analyses. In vitro experiments revealed that this peptide effectively enhanced enamel resistance to acid-induced erosion compared to control treatments. These results suggest the potential of DDSt15, particularly at the concentration of 0.94 × 10⁻⁵ M, to contribute to the development of strategies for acquired pellicle modulation aimed at preventing intrinsic enamel erosion.